Trifolium repens extracts as a green corrosion inhibitor for carbon steel in a 3.5% NaCl solution - Nour El Houda, Sobhi; Amel, Boukhouiete; Malika, Foudia (Journal of the Taiwan Institute of Chemical Engineers, 2024)
•Trifolium repens is a green alternative to toxic corrosion inhibitors.•The inhibitor achieves 98 % inhibition efficiency at 20 ppm in 3.5 % NaCl medium and acts as a mixed-type inhibitor with a strong cathodic effect.•The corrosion inhibition mechanism is driven by physical adsorption of the inhibitor onto the metal surface, following the langmuir adsorption isotherm.•Trifolium repens forms a protective layer which is confirmed by electrochemical and surface analyses. Material degradation is a major issue that has been the subject of intense research and investigation by the scientific community. It has harmful consequences that require serious and careful intervention. However, restrictions on the use of inhibitors containing toxic compounds pose a significant challenge to the implementation of effective corrosion treatments. This has necessitated a continuous search for new and innovative ways to protect against material damage. Plant-derived natural inhibitors offer several advantages, including potent inhibitory effects, lack of toxicity, biodegradability, and environmentally sustainable origins. The purpose of this research was to evaluate the corrosion resistance of API5LX60 carbon steel in a 3.5 % NaCl environment using Trifolium repens as an environmentally friendly inhibitor. The inhibitor extract was analysed using Fourier Transform Infrared (FTIR) spectroscopy. However, gravimetry and electrochemical methods (potentiodynamic polarization and electrochemical impedance spectroscopy (EIS)) were used to investigate the corrosion behaviour. Scanning electron microscopy (SEM) and atomic force microscopy (AFM) were used to examine the surface morphology. After testing a range of concentrations in a 3.5 % NaCl medium, the highest level of inhibition (98 %) was obtained at 20 ppm, confirming the mixed action of the inhibitor with predominantly cathodic action. The inhibition mechanism involved physical adsorption on metal surfaces according to the Langmuir model, which enhances the corrosion-inhibiting ability; the extract forms a protective layer that successfully inhibits corrosion, as confirmed through electrochemical and surface analysis. These results demonstrate that the extract acts as a potent anticorrosive agent. [Display omitted]